The most favoured nation and non-discrimination provisions in international trade law and the OECD codes of liberalisation - Marín Odio, Andrea (OECD Working Papers on International Investment, 2020)
Increasing moves away from multilateralism have created a fragmented trade and investment scenario where economies progressively combine the application of restrictive unilateral actions with bilateral and regional preferences. The application of, and exceptions to, the non-discrimination provisions are a fundamental element of these trends. This paper sheds light on the two types of non-discrimination provisions considered the founding stones of the multilateral system: the most favoured nation (MFN) clause - as developed under the GATT and GATS - and the non-discrimination clause among countries adhering to the OECD Codes of Liberalisation. While not taking a position on the complex question of whether a multilateral, plurilateral or bilateral approach to trade and investment liberalisation should be pursued, the paper illustrates the OECD has upheld the non-discrimination obligation as one of its basic principles, dating back to its origins over 60 years ago